Determinant of Macroeconomic Variables on Foreign Exchange Reserves in Indonesia - Rifda Syahda Nabilah; Mahrus Lutfi Adi Kurniawan; Fitra Pasapawidya Purna (INCOME: Innovation of Economics and Management, 2025)
The research aims to analyze the influence of macroeconomic variables on foreign exchange reserves in Indonesia. This cannot be separated from the fact that the accumulation of foreign exchange reserves is very closely related to the condition of macroeconomic variables. The research uses time-series data from 2019:M01-2023:M12. The multiple linear regression approach is applied to determine the influence of the independent variable on the dependent variable in the foreign exchange reserve model. The research results show that imports, inflation and the exchange rate have a negative effect on foreign exchange reserves. An increase in these three variables will reduce foreign exchange reserves. The money supply has a positive effect on the exchange rate. The OLS approach produces BLUE regression, because the model is free from classical assumption problems. The implication of the research is that the government needs to implement an expansionary fiscal policy by increasing government spending, encouraging exports and maintaining the stability of the rupiah exchange rate against the US dollar. Stable domestic economic conditions will have an impact on increasing the accumulation of foreign exchange reserves.